Uma “árdua” missão: trajetória política do general Ferdinando de Carvalho no combate ao comunismo (1960-1980) - Santos, Paula Eloise dos (2025)
This dissertation investigates the political trajectory of General Ferdinando de Carvalho during the National Security Dictatorship, highlighting his role as an ideologue of anti-communism and an agent of repression against the Brazilian Communist Party. The study examines how Carvalho operationalized the National Security Doctrine and the Revolutionary Warfare Doctrine, transforming theoretical principles into practices of political persecution that combined legal formalism and arbitrary violence. His role in Military Police Inquiry No. 709 and in dismantling the State Committee of the PCB in Paraná exemplifies this method, with records of systematic torture. The analysis of his trajectory contributes to understanding the mechanisms of State Terrorism in Brazil and the persistent challenges in overcoming the authoritarian legacy, since, after the dictatorship, his impunity and highlight the limitations of Brazilian redemocratization. By elucidating the relationships between intellectual production and state violence, the research engages with academic and public debates on memory, transitional justice, and the power structures that continue to shape social relations in the present.